THE INFLUENCE OF BLENDED LEARNING ON LEARNING OUTCOMES - Walib Abdullah; Abdul Halim; R Fahmi Ali (STIT Al - Ibrohimy Bangkalan, 2023)
Blended learning is one of learning methods that combines learning technology with actual work assignments to create a positive impact on learning and work which means 50% face-to-face learning and 50% online learning, it can also use 75/25 that we can use 75% face-to-face learning and 25% online learning from time allocation, and also it can combine 25/75 means 25% face-to-face learning and 75% online learning. This research used an experimental method of quasi-experimental pretest-posttest none-evaluative control group design. The sample in this research was 21 respondents divided into 2 classes namely the experimental class and the control class The experimental class uses blended learning while the control class uses conventional learning . based on the results of the paired sample T test sig value (2 tailed) 0,000 <0.005, it can be concluded that there is the effect of blended learning on learning outcomes While the results of the independent sample T test 0,000 <0,005 then there is a difference between blended learning with conventional learning with an average blended learning of 83,76 while conventional learning is 77,67 then showing blended learning is more effective or greater influence than conventional learning.